Important Non-Wood Forest Products in Turkey: An Econometric Analysis - Kurt, Rıfat; Karayılmazlar, Selman; Çabuk, Yıldız; Çabuk, Yıldız; Karayılmazlar, Selman; Kurt, Rıfat (Eos Assoc, 2016)
Wood resources obtained from forest and non-wood forest products (NWFP) have gained great importance recently as their economic values keeps increasing by the day. In this study, forecasting of Turkish Non-Wood Forest Products such as thyme, bay leaves, salvia and pine nut export amounts was carried out using a linear regression analysis method for the next fifteen years based on the data for the years between 1990 and 2009. Moreover, estimated import values and actual import values from the last years were compered and analyzed. Finally, predictions on future trends were made.
Keywords: Regression; Export; Thyme; Bay Leaves; Salvia; Pine Nut